2020
DOI: 10.1002/oby.22848
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cardiometabolic Risk Factors Before and After Gestational Diabetes: A Prospective Life‐Course Analysis in CARDIA Women

Abstract: This study hypothesized that both preconception and postchildbearing patterns of cardiometabolic risk factors may be different for women with gestational diabetes mellitus (GDM) compared with women without GDM. Methods: Among 1,302 (51% black) women in the Coronary Artery Risk Development in Young Adults (CARDIA) study with births and followed for 30 years, this study evaluated changes in cardiometabolic factors (BMI, waist circumference [WC], lipids, blood pressure) during prechildbearing (prior to the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…Searches identified 24,027 studies following removal of duplicates; 945 full texts were screened for eligibility, of which 70 20,21,37–104 met the inclusion criteria (Figure S1). Of these studies, 59 were cohort and 11 were case control studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Searches identified 24,027 studies following removal of duplicates; 945 full texts were screened for eligibility, of which 70 20,21,37–104 met the inclusion criteria (Figure S1). Of these studies, 59 were cohort and 11 were case control studies.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies reported associations between measures of WC and a diagnosis of GDM 46,51,55,57–60,72,77,83,86,88,97,103 and 16 reported case control data for early pregnancy WC between women diagnosed with GDM during pregnancy (cases) and women not diagnosed with GDM (controls) 37,46–48,52,57–60,67,73,78,80,83,88,103 . Nine studies reported categorical measures of WC 37,46,51,55,57,58,60,83,86,103 and eight could be pooled in the meta‐analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women who develop GDM already have higher BMIs and worse metabolic profiles before pregnancy, which includes higher total cholesterol, triglycerides, and homeostatic model assessment for insulin resistance and lower high-density lipoprotein cholesterol [ 62 , 63 ]. Immediately after delivery, women with a previous history of GDM are more obese and have a higher prevalence of metabolic syndrome [ 64 , 65 ]. Over time after delivery, the annual increases in BMI, blood pressure, and total cholesterol did not differ between women with and without GDM.…”
Section: Maternal Complications Of Gdmmentioning
confidence: 99%
“…Over time after delivery, the annual increases in BMI, blood pressure, and total cholesterol did not differ between women with and without GDM. Therefore, women with a previous history of GDM persistently have worse cardiometabolic risk factors than women without GDM over time [ 64 ]. As a result, women with a previous history of GDM have increased coronary artery calcium scores and carotid intima media thickness, which are surrogates for atherosclerosis and future CVD, after delivery [ 66 , 67 ].…”
Section: Maternal Complications Of Gdmmentioning
confidence: 99%